Adolescents Conflicts Resolution Patterns: A Descriptive Analysis - Apriyeni, Emira; Patricia, Helena; Rahayuningrum, Dwi Christina (PT. Riset Press International, 2024)
Adolescence is a critical period and is vulnerable to experiencing conflict in everyday life. Therefore, appropriate conflict resolution is needed for adolescents to avoid social problems. Conflict resolution is a problem-solving process that considers the needs of diverse individuals. The research aims to see a picture of conflict resolution in adolescents. This type of research is descriptive and was conducted at Senior High School in Padang City. The research was conducted for one week on 24 respondents using a purposive sampling technique. Data were collected using a questionnaire via form for students. Univariate data analysis uses frequency distribution. The research results showed that more than half of the respondents (54.2%) carried out conflict resolution destructively. It can be concluded that adolescents still use destructive resolutions in dealing with conflicts in everyday life. It is hoped that teenagers will be able to find ways to resolve conflicts so that they can improve mental health in adolescents.